Legality, Certainty, and Judicial Omission of Financial Penalties in Narcotics Sentencing: Evidence from Indonesia - Yabes Jonathan Sitorus; Dewi Sulistianingsih; Martitah Martitah (Islamic Studies and Development Center in Collaboration With Students' Research Center Universitas Negeri Padang, 2026)
This study examines judicial interpretation of criminal sanctions under Article 132 paragraph (1) of Law Number 35 of 2009 on Narcotics by analyzing the District Court of Tebing Tinggi Decision Number 174/Pid.Sus/2025/PN Tbt. The central issue concerns the court’s omission of financial penalties despite the fact that the principal offense referred to particularly Article 114 paragraph (1) explicitly mandates a cumulative sanction system combining imprisonment and fines. Using doctrinal legal research, the study finds that the judge’s reliance solely on grammatical interpretation disregarded the systematic construction and normative purpose of narcotics sentencing, which regards financial sanctions as an imperative element. Such interpretation not only undermines the principles of legality and legal certainty but also weakens the effectiveness of criminal policy in addressing narcotics offenses as extraordinary crimes. This research highlights the necessity of systematic statutory interpretation and recommends normative refinements, including clearer sentencing guidelines, to prevent future disparities in judicial decisions.